Accommodation decision-making for postsecondary students with ADHD: Implications for neuropsychologists. Issue 4 (21st April 2021) - Weis, Robert; Hombosky, Marisa L.; Schafer, Kendra K.; Shulman, Darcy; Tull, Jessica K.
ABSTRACT: Neuropsychologists are often asked to evaluate students for attention-deficit/hyperactivity disorder (ADHD) and to provide documentation to support their requests for academic accommodations in college. Research points to the importance of multi-method, multi-informant data when evaluating ADHD and determining the need for accommodations. However, the Association on Higher Education and Disability (AHEAD) directs disability service providers to give primacy to students' self-reports and their own impressions of students' narratives over objective, third-party data when rendering accommodation decisions. The organization asserts that in many cases information from parents, teachers, and psychologists is not needed to confirm the existence of a disability or students' need for accommodations. In this article, we describe the way disability service providers are directed to evaluate accommodation requests, the limitations of these procedures, and the dangers of well-intentioned, but indiscriminate accommodation-granting. We then provide recommendations for neuropsychologists who conduct ADHD evaluations for college students in light of these professional guidelines.